2021
DOI: 10.3389/fmars.2021.545217
|View full text |Cite
|
Sign up to set email alerts
|

Digestive Tract and the Muscular Pharynx/Esophagus in Wild Leptocephalus Larvae of European Eel (Anguilla anguilla)

Abstract: Several aspects of the biology of European eel (Anguilla anguilla) larvae are still unknown; particularly, information about their functional development and feeding is sparse. In the present study, we histologically characterize the digestive system of wild caught specimens of European eel leptocephalus larvae. The aim was to provide more understanding about how food may be ingested and mechanically processed in the leptocephalus larvae, and to discuss this in the context of its hypothesized feeding strategy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Furthermore, it has been reported that high‐molecular‐mass proteins accumulate in the posterior part of the intestinal tract and that pinocytosis and intracellular digestion occur (Tanaka, 1972; Watanabe, 1982). In eel larvae, active transport of water and solutes also occurs in the midgut epithelium; furthermore, the hindgut epithelium appears to be similarly involved in the uptake of undigested macromolecules and intracellular digestion (Knutsen et al ., 2021; Otake, 1996). In other words, the reflux, retention and solidification of Synechococcus cells in the mid‐hindgut confirmed in this study are very interesting because the observations seem to be consistent with previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that high‐molecular‐mass proteins accumulate in the posterior part of the intestinal tract and that pinocytosis and intracellular digestion occur (Tanaka, 1972; Watanabe, 1982). In eel larvae, active transport of water and solutes also occurs in the midgut epithelium; furthermore, the hindgut epithelium appears to be similarly involved in the uptake of undigested macromolecules and intracellular digestion (Knutsen et al ., 2021; Otake, 1996). In other words, the reflux, retention and solidification of Synechococcus cells in the mid‐hindgut confirmed in this study are very interesting because the observations seem to be consistent with previous findings.…”
Section: Discussionmentioning
confidence: 99%